From Judaica Collections to Zionist Exhibitions - Kamczycki, Artur (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
For religious Jews in medieval and modern times, art – in the Western European sense – was an irrelevant and unnecessary issue for life, because traditional Judaism, observing the second commandment of the Mosaic Decalogue, rejected its existence as an object of adoration and “delight”. (Exodus 20:4). In religious culture, art and creativity can only be understood in the context of artistic craftsmanship, and its characteristic feature is the symbolic and decorative aspect. Moreover, in religious circles there is a lack of concepts of the autonomy of the artwork and its contemplation as well as a definition of artistic creation. Nevertheless, since the Middle Ages (12th century) there has been a custom of collecting religious exhibits in synagogues, and the activity of individual collectors of Judaica dates back to the 17th century. The turn of the 19th and 20th centuries marked the beginning of the Zionist movement, in whose program – following the European model – art was to be an element of building a new ( Jewish) identity, and collections of old Judaica were included in this process. Henceforth, it was assumed that visual arts would be fully used for the purposes of the so-called promotion of Zionism and its demands, as well as starting a debate on the role, function and possibilities of impact of visual arts. Therefore, within the framework of Zionism, not only was the theory of art reevaluated (and its universal adaptation), but, above all, it was harnessed to specific goals and the projection of postulates calling for the formation of a separate national and Zionist consciousness. We can therefore repeat after Kalman Bland that “What complicates the argumentation of Jewish Aiconism is late-nineteenth-century Zionism.” It should also be added, following Steven Fine, that: “Israel begins its adventure with art only in the centenary of Zionism”.